TRANSLATION AND INTERPRETATION OF BEHAVIORAL VERBS FROM UZBEK INTO ENGLISH - Elchayev Zokhidjon Akhmatovich (Bright Mind Publishing, 2026)
The translation of behavioral verbs from Uzbek to English presents intricate linguistic challenges due to semantic ambiguity, syntactic differences, and cultural specificities embedded in both languages. This study investigates these challenges through corpus analysis and translator interviews. Findings reveal that translators often navigate polysemy, verb valency shifts, and pragmatic nuances, requiring adaptive strategies such as modulation, compensation, and restructuring to maintain semantic accuracy and communicative intent. The results offer important insights for translation theory and pedagogy, emphasizing the need for cultural and linguistic competence in translating behavioral verbs effectively.
Keywords: Behavioral verbs, Uzbek-English translation, semantic ambiguity, syntactic differences, pragmatic translation, translation strategies, cross-cultural communication, translator competence, polysemy in translation, modulation and compensation.